2008
DOI: 10.3323/jcorr.57.194
|View full text |Cite
|
Sign up to set email alerts
|

Galvanic Corrosion of Anodized Aluminum-Influence of Anodic Oxide Film Structure and Concentration of Cl--

Abstract: The effect of anodic oxide film structure, barrier type and porous type on galvanic corrosion resistance of aluminum in 0.5 kmol/m 3 H 3 BO 3 / 0.05 kmol/m 3 Na 2 B 4 O 7 with NaCl was examined by electrochemical random signal (electrochemical noise) analysis technique. When pitting corrosion occurs, rest potential suddenly decreases and current increases rapidly, and rest potential and current change with fluctuation during galvanic corrosion. The galvanic current change correlates closely with corrosion pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…Some research on the effect of metal cations on corrosion behavior of steels have been reported, and here corrosion behavior changes with the kind of the metal cations in solutions [15][16][17]. Some of the authors also investigated the effect of metal cations on the corrosion behavior of A3003 in model tap waters [18][19][20][21][22], and it was found that the corrosion behavior of A3003 strongly depends on the kinds of metal cations in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Some research on the effect of metal cations on corrosion behavior of steels have been reported, and here corrosion behavior changes with the kind of the metal cations in solutions [15][16][17]. Some of the authors also investigated the effect of metal cations on the corrosion behavior of A3003 in model tap waters [18][19][20][21][22], and it was found that the corrosion behavior of A3003 strongly depends on the kinds of metal cations in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…이러한 사 회적 이슈로 FRP나 철강 재료가 주를 이루는 중소 형 선박의 대체 소재로 알루미늄이 각광을 받고 있 다 [1][2][3] . 그러나 알루미늄 선박의 수명 연장을 위한 열처리, 성분 첨가 등의 꾸준한 노력에도 불구하고 여전히 가혹한 해양환경에서의 부식 및 고속으로 인한 침식 문제가 발생하고 있다 4) .…”
Section: 서 론unclassified
“…The authors used hardness of cations, X, which based on HSAB concepts to explain the degree of the incorporation quantitatively 10) . The results showed that the corrosion rate of aluminum alloys tends to decrease with increase in X [11][12][13][14] . However, the effect of metal cations on the corrosion mechanism of the alloy was not clari ed.…”
Section: Introductionmentioning
confidence: 98%